MicroRNA‐503‐5p inhibits stretch‐induced osteogenic differentiation and bone formation. (19th December 2016) - Liu, Lu; Liu, Mengjun; Li, Rongrong; Liu, Hong; Du, Liling; Chen, Hong; Zhang, Yan; Zhang, Shijie; Liu, Dongxu
Abstract: Cyclical stretch‐induced bone formation during orthodontic treatment is a complex biological process modulated by various factors including miRNAs and their targeted‐gene network. However, the miRNA expression profile and their roles in osteogenic differentiation of bone mesenchymal stem cells (BMSCs) exposed to mechanical stretch remains unclear. Here, we use the miRNA microarray assay to screen for mechano‐sensitive miRNAs during stretch‐induced osteogenic differentiation of BMSCs and identified that nine miRNAs were differentially expressed between stretched and control BMSCs. Furthermore, miR‐503‐5p, which was markedly downregulated in both microarray assay and qRT‐PCR assay were selected for further functional verification. We found that overexpression of miR‐503‐5p in BMSCs attenuated stretch‐induced osteogenic differentiation while the effect was reversed by miR‐503‐5p inhibition treatment. In vivo studies, overexpression of miR‐503‐5p with specific agomir decreased Runx2, ALP mRNA, and protein expression, decreased osteoblast numbers and osteoblastic bone formation in the OTM tension sides. In conclusion, our study revealed that miR‐503‐5p functions as the mechano‐sensitive miRNA and inhibits BMSCs osteogenic differentiation subjected to mechanical stretch and bone formation in OTM tension sides.